1987
DOI: 10.1113/jphysiol.1987.sp016371
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of reticulo‐ruminal motility by volatile fatty acids and lactic acid in sheep.

Abstract: SUMMARY1. A study was made of the influence on reticulo-ruminal motility, recorded by electromyography, of ruminal infusions of volatile fatty acids (VFAs) and lactic acid in twenty-four sheep maintained by intragastric infusion of a complete liquid diet, in three sheep fed grass pellets, and in nine chronically vagotomized sheep; abomasal and duodenal infusions of VFA and lactic acid were tested in five sheep fed grass pellets.2. Ruminal infusions of VFAs and lactic acid progressively inhibited the amplitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
13
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 20 publications
3
13
0
Order By: Relevance
“…15 nimi) in the terminial ileum about 30 cm from the ileo-caecal junctioll and(l three others were fittedl w%ith a rumen canniula (polypropylene, 17 mm diameter). All surgery w-as performe(l und(ler aseptic conditions under halothane anaesthesia as previously dlescribe(l (Gregory. 1987).…”
Section: Methodsmentioning
confidence: 99%
“…15 nimi) in the terminial ileum about 30 cm from the ileo-caecal junctioll and(l three others were fittedl w%ith a rumen canniula (polypropylene, 17 mm diameter). All surgery w-as performe(l und(ler aseptic conditions under halothane anaesthesia as previously dlescribe(l (Gregory. 1987).…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Some authors have manipulated the ration fed in an effort to influence VFA concen-trations in the digestive tract, [1][2][3][4][5] whereas others have used cannulas to infuse VFA solutions directly into the gastrointestinal segment of interest. [1][2][3][4][5][6][7][8] Some authors have manipulated the ration fed in an effort to influence VFA concen-trations in the digestive tract, [1][2][3][4][5] whereas others have used cannulas to infuse VFA solutions directly into the gastrointestinal segment of interest.…”
mentioning
confidence: 99%
“…In the course of these studies, it has been suggested that mucosal nervous elements may play a role in sensory reception (mechanoand chemo-receptors) of the forestomach (LEEK and HARDING, 1975;LEEK, 1986). Intrinsic nerve reflexes via the enteric nervous system of the ruminant forestomach in response to chemical stimuli from the lumen also have been proposed (GREGORY, 1982(GREGORY, , 1984(GREGORY, , 1987COTTRELL and GREGORY, 1991).…”
mentioning
confidence: 99%